A new dimension for deployment: Strategic development for 3D printing. Issue 6 (2nd May 2019) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoints the practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: There is often a disconnect between science and business that is hard to fathom. Sometimes, of course, it is easy to see why two parties can seem so far apart – the scientist in search of truth and uninterested in any practical or commercial use of an invention – the industrialist who is dedicated to one course of action and unwilling to learn from research, which can prove it is the wrong one. Both people are as guilty as each other of missing what is staring them in the face. And yet, this dogged pursuit of a single goal is what represents them and perhaps enables them to more successful than other at what they choose to do. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.